2020
DOI: 10.3847/1538-4357/ab9b7e
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Features in Field-aligned Solar Wind Turbulence from Parker Solar Probe Observations

Abstract: Parker Solar Probe (PSP) observed a large variety of Alfvénic fluctuations in the fast and slow solar wind flow during its two perihelia. The properties of Alfvénic solar wind turbulence have been studied for decades in the near-Earth environment. A spectral index of −5/3 or −2 for magnetic field fluctuations has been observed using spacecraft measurements, which can be explained by turbulence theories of nearly incompressible magnetohydrodynamics (NI MHD) or critical balance. In this study, a rigorous search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 48 publications
6
53
3
Order By: Relevance
“…Telloni et al (2019) identified 17 highly field-aligned fast solar wind flow intervals of length > 1 hour by searching 12 years of Wind measurements, finding that these intervals admitted a Kolmogorov-type of power law k −5/3 || during strong turbulence. Zhao et al (2020) found two highly field-aligned intervals of ∼ 20 minutes in the slow solar wind in the first and second encounters of PSP, and, similar to Telloni et al (2019), find that the turbulence is unidirectional (σ c ∼ −1) and exhibits a Kolmogorov-like spectrum in the parallel wavenumber, that is with a k −5/3 || power law. In this manuscript, we study the evolution of the variance anisotropy (Belcher & Davis 1971;Pine et al 2020) of the energy in forward and backward propagating modes, the fluctuating magnetic energy, and the fluctuating kinetic energy in the fast and slow solar wind in the inner heliosphere using Solar Orbiter measurements and interpret the results in terms of the nearly incompressible magnetohydrodynamic (NI MHD) turbulence transport model equations (Zank et al 2017).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Telloni et al (2019) identified 17 highly field-aligned fast solar wind flow intervals of length > 1 hour by searching 12 years of Wind measurements, finding that these intervals admitted a Kolmogorov-type of power law k −5/3 || during strong turbulence. Zhao et al (2020) found two highly field-aligned intervals of ∼ 20 minutes in the slow solar wind in the first and second encounters of PSP, and, similar to Telloni et al (2019), find that the turbulence is unidirectional (σ c ∼ −1) and exhibits a Kolmogorov-like spectrum in the parallel wavenumber, that is with a k −5/3 || power law. In this manuscript, we study the evolution of the variance anisotropy (Belcher & Davis 1971;Pine et al 2020) of the energy in forward and backward propagating modes, the fluctuating magnetic energy, and the fluctuating kinetic energy in the fast and slow solar wind in the inner heliosphere using Solar Orbiter measurements and interpret the results in terms of the nearly incompressible magnetohydrodynamic (NI MHD) turbulence transport model equations (Zank et al 2017).…”
Section: Introductionsupporting
confidence: 56%
“…In the second method, Pine et al (2020) computed the anisotropy from the distribution of energy between parallel and perpendicular wavevectors. The results show that the anisotropy does not depend on the direction of the mean magnetic field relative to the radial direction (see also Tessein et al that is observed by WIND and Parker Solar Probe (PSP) in highly field-aligned flows (σ c ∼ ±1) (Telloni et al 2019;Zhao et al 2020). This result is quite distinct from the prediction of critical balance theory (Goldreich & Sridhar 1995), which requires σ c ∼ 0.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The plasma wave modes reported in this region of space include narrowband waves such as ion cyclotron waves (Bowen et al 2020;Verniero et al 2020), whistler-mode waves (Agapitov et al 2020;Jagarlamudi et al 2020;Cattell et al 2021), Langmuir waves (Bale et al 2019), ion acoustic waves (Mozer et al 2020), and waves near the electron cyclotron frequency (Malaspina et al 2020). Broadband waves have also been reported, including kinetic Alfvén waves (Chaston et al 2020) and plasma turbulent fluctuations (Chen et al 2020;Zhao et al 2020;Zhu et al 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Using abbreviations k ⊥ and k P for perpendicular and parallel wavevector components, the first geometry consists of oblique fluctuations with k ⊥ > k P and the second geometry exhibits fluctuations that are more field aligned (k ⊥ < k P ) with lower amplitudes. A possible interpretation of this finding is the simultaneous coexistence of two-dimensional (2D) (k P ∼ 0) turbulent and slab (k ⊥ ∼ 0) fluctuations (e.g., Verscharen et al 2019;Zhao et al 2020a). In the strict sense, purely 2D turbulence is characterized by a wavevector exactly perpendicular to the background magnetic field, B0, whereas purely slab turbulence is characterized by a wavevector exactly parallel to B0; however, these extreme situations are very rare in the solar wind, meaning that the power of these fluctuations is distributed across a finite range of angles around the 2D and slab limits.…”
Section: Introductionmentioning
confidence: 99%